Synergistic Antihyperglycemic and Antihyperlipidemic Effect of Polyherbal and Allopolyherbal Formulation - Yahya Alhamhoom; Syed Sagheer Ahmed; Rupesh Kumar M.; MD. Salahuddin; Bharathi D. R.; Mohammed Muqtader Ahmed; Syeda Ayesha Farhana; Mohamed Rahamathulla (MDPI AG, 2023)
Polyherbal formulation (PHF) enhances therapeutic efficacy and minimizes side effects by reducing individual herb dosages. Allopolyherbal formulation (APHF) combines polyherbal extracts with allopathic medication, effectively reducing the latter's required dose and mitigating associated adverse effects. The current study intends to assess the anti-diabetic effects of PHF and APHF in-vivo. Dried raw powders of Cassia auriculata leaf, Centella asiatica leaf, and Zingiber officinale rhizome were extracted by cold maceration process using 70% ethanol. These extracts were combined in three different ratios to make PHF. PHF was subjected to qualitative and quantitative phytochemical investigations. APHF has been prepared by combining a potent ratio of PHF with metformin in three different ratios. The compatibility of APHF has been confirmed by differential scanning calorimetry (DSC). In vivo activity was also evaluated in streptozotocin-induced diabetic albino rats. PHF (3 different ratios at a dose of 200-400 mg/kg b.w), APHF (combination of PHF and metformin in 3 different ratios, 200 + 22.5, 200 + 45, and 200 + 67.5 mg/kg b.w), and metformin (90 mg/kg b.w) were administered to albino rats for 21 consecutive days. Blood glucose levels were estimated on the 1st, 7th, 14th, and 21st days of treatment. On the 21st day, blood was collected by cardiac puncture for biochemical analysis. The liver and pancreas were isolated and subjected to histopathological analysis. PHF and APHF showed significant anti-diabetic and antihyperlipidemic efficacy. In comparison to PHF, APHF had the most promising action. The current study demonstrated that PHF and APHF are safe and efficacious drugs in the treatment of diabetes mellitus as they help to replace or lower the dose of metformin, thereby decreasing the risks of metformin.